2016
DOI: 10.17795/nmsjournal32990
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spiritual Intervention on Postmenopausal Depression in Women Referred to Urban Healthcare Centers in Isfahan: A Double-Blind Clinical Trial

Abstract: Background:Depression is not only common after menopause, but also affects postmenopausal women more than other women. Some studies show the positive effects of spiritual intervention on postmenopausal women and depressed patients. However, there is inadequate experimental data for supporting the effectiveness of such interventions.Objectives:This study investigated the effect of a spiritual intervention on postmenopausal depression in women referred to urban healthcare centers in Isfahan, Iran.Patients and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Regarding health-promoting behavior subscales, it was observed that the highest scores were in spiritual health, one of the most essential aspects of human health as it provides people with meaning and direction in life, as well as traits such as life stability, peace, and a sense of closeness to oneself, God, and others ( 30 , 31 ). The current result could interpret in form of the important rules of the Islamic religion and spiritual enhancement in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding health-promoting behavior subscales, it was observed that the highest scores were in spiritual health, one of the most essential aspects of human health as it provides people with meaning and direction in life, as well as traits such as life stability, peace, and a sense of closeness to oneself, God, and others ( 30 , 31 ). The current result could interpret in form of the important rules of the Islamic religion and spiritual enhancement in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…They recommended further studies on the effect of vitamin C on anxiety and depression among postmenopausal women. Shafiee et al ( 28 ) indicated that spiritual interventions were effective in reducing depression and improving the psychological dimension among postmenopausal women. Their study was inconsistent with the present one regarding the psychological dimension.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, about 73.6% of women experiencing menopause in Turkey ( 15 ) and 70% of women with polycystic ovary syndrome ( 16 ) in Australia used CAM. Studies showed that dry and wet cuppings ( 17 ), acupuncture ( 18 ), acupressure ( 19 ), massage ( 20 ), relaxation ( 21 ) and yoga ( 22 ), aromatherapy ( 23 ), diets ( 24 ), homeopathy ( 25 ), music therapy ( 26 ), hydrotherapy ( 27 ), and prayer ( 28 ) affected the improvement of vasomotor symptoms, urogenital disorders, fatigue, and depression caused by menopause. In addition, herbal products, such as chamomile ( 29 ), Vitex agnus-castus ( 30 ), Hypericum Perforatum ( 31 ), Crocus sativus ( 32 ), Curcumin ( 33 ), Melissa Officinalis ( 34 ), Thymes ( 35 ), Wheat Germ ( 36 ), Fennel (Foeniculum vulgare) ( 37 ), Valerian Root ( 38 ), Ginger ( 39 ) and Flaxseed ( 40 ), and Soy Isoflavones ( 41 ) affected physical and psychological symptoms caused by menopause.…”
Section: Introductionmentioning
confidence: 99%
“…Also, royal jelly is substantially used in the cosmetic industry due to its inhibitory effect on sebum secretion and, consequently, its impact on acne formation, acne-induced lesions, and small wounds [ 12 ]. Several preclinical and clinical studies demonstrated royal jelly’s therapeutic role against multiple sclerosis [ 13 ], traumatic brain injury [ 14 ], and infertility [ 15 ]. Nevertheless, the culminating effect of royal jelly was noted to alleviate premenstrual syndrome and menopause in females [ 16 , 17 ] and maintain the blood lipid profile [ 18 ].…”
Section: Introductionmentioning
confidence: 99%